The British miner in the age of de-industrialization : a political and cultural history - Arnold, Jörg, 1973- 1973- (Oxford University Press, 2024)
A book which challenges received understandings of the place of the miner in contemporary British history, arguing that the British coal miners went through a cyclical movement -- from loser to winner and back again -- as Britain underwent a de-industrial revolution in the final decades of the twentieth century